2020
DOI: 10.21203/rs.3.rs-51708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Pre-Workout Multi-Ingredient Supplement on Anaerobic Performance: Randomized Double-Blind Crossover Study

Abstract: Background: The purpose of this study was to investigate the acute effects of commercially available pre-workout supplement on anaerobic performance in resistance trained men.Methods: Twenty-three men underwent three testing sessions administrated in a randomized and double-blind fashion separated by a seven-day break. The participants performed three exercise tests: isokinetic strength test, maximal strength test and Wingate test. Statistical analysis was conducted in R environment. Linear mixed models were e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…That might be due to the group involvedyoung, recreationally-trained handball male players students but not experienced athletes, for which the range of the results would probably be more stable. It can also be postulated, that the significant difference between PL and MIPS group is due to the synergistic effect of caffeine and other constituents of the pre-workout ingredients (6,19). There is very limited data on the effect of acute MIPS ingestion and its effect on lower limbs power measured by CMJ or vertical jump.…”
Section: Discussionmentioning
confidence: 99%
“…That might be due to the group involvedyoung, recreationally-trained handball male players students but not experienced athletes, for which the range of the results would probably be more stable. It can also be postulated, that the significant difference between PL and MIPS group is due to the synergistic effect of caffeine and other constituents of the pre-workout ingredients (6,19). There is very limited data on the effect of acute MIPS ingestion and its effect on lower limbs power measured by CMJ or vertical jump.…”
Section: Discussionmentioning
confidence: 99%
“…Kaczka et al [ 8 ] have demonstrated that supplements including caffeine have a positive effect on anaerobic activities, especially in delaying fatigue and increasing strength. Madden et al [ 9 ] also found that the rating of perceived exertion and physical performance was higher in the group of individuals ingesting caffeine.…”
Section: Introductionmentioning
confidence: 99%